An investigation into the barriers preventing the implementation of the surgical safety checklist in the operating room in tertiary hospitals in the Cape Metropole - Koopman, Gerda (Stellenbosch : Stellenbosch University, 2018)
Thesis (MCur)--Stellenbosch University, 2018.